New characterization of Morrey spaces - Gogatishvili, Amiran; Mustafayev, Rza (Eurasian Mathematical Journal, 2013)
In this paper we prove that the norm of the Morrey space Mp,λ is equivalent to an expression involving integrals over balls and their complements. We investigate the relationships between local Morrey-type spaces and complementary local Morrey-type spaces, including their associate and dual spaces.